2021
DOI: 10.3390/ijerph18073355
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Brazilian Immigrant Community in the U.S: Results from a Qualitative Study

Abstract: While an increasing body of data suggests that marginalized groups have been disproportionately impacted by COVID-19, little has been published about the specific impact on Brazilian immigrants in the U.S. We conducted 15 key informant interviews, one of which included two participants (n = 16), with representatives from social service agencies, healthcare, and faith-based organizations serving Brazilian immigrants. Key informants were asked about the community’s experiences with COVID-19 testing and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…We also found that those who had high levels of trust in health information from healthcare providers were more likely to have positive vaccine intentions, while those who trusted social networks and private news sources were more likely to report that they would not get the vaccine or were unsure [ 50 , 51 ]. Other studies have similarly found that physicians are trusted sources of health information and can serve as important cues to action to promote COVID-19 vaccine uptake among general populations [ 21 , 34 , 40 , 41 ], and we found this in a prior qualitative study among Brazilian immigrants [ 52 ]. To strengthen the impact of health information among the Brazilian population, healthcare providers should ensure health communication regarding COVID-19 vaccination is culturally competent (e.g., tailored to meet people’s social, cultural, and linguistic needs) [ 8 , 53 ].…”
Section: Discussionsupporting
confidence: 67%
“…We also found that those who had high levels of trust in health information from healthcare providers were more likely to have positive vaccine intentions, while those who trusted social networks and private news sources were more likely to report that they would not get the vaccine or were unsure [ 50 , 51 ]. Other studies have similarly found that physicians are trusted sources of health information and can serve as important cues to action to promote COVID-19 vaccine uptake among general populations [ 21 , 34 , 40 , 41 ], and we found this in a prior qualitative study among Brazilian immigrants [ 52 ]. To strengthen the impact of health information among the Brazilian population, healthcare providers should ensure health communication regarding COVID-19 vaccination is culturally competent (e.g., tailored to meet people’s social, cultural, and linguistic needs) [ 8 , 53 ].…”
Section: Discussionsupporting
confidence: 67%
“…Another possible explanation is that Chinese women in Japan were limited due to their immigrant status, with economic difficulties and language barriers, which are associated with a low mental health level. A finding among Brazilian immigrants reported a similar psychological burden [15].…”
Section: Discussionmentioning
confidence: 77%
“…Immigrant women, as a minority group, experienced more mental health problems than native women [14]. A qualitative study on the immigrant community in the United States (U.S.) reported that the COVID-19 pandemic affects immigrants' mental health and interpersonal relationships [15]. We inferred that immigrant women in Japan might experience a low level of mental health status due to the outbreak of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 91%
“…These impacts are driven by factors such as their tendency to work in jobs where they face higher risks of exposure to the virus as well as their inability to work from home due to the uncertainties associated with insecure work contracts (Gelatt, 2020; Quandt et al., 2020). Other studies have specifically been concerned about how these impacts could accentuate the disadvantage of immigrants (Gonzalez et al., 2020; Langellier, 2020; Priebe et al., 2021). Indeed, there is now increasing evidence on the diverse hardships faced by immigrant communities as a result of the pandemic.…”
Section: Introductionmentioning
confidence: 99%